Pendampingan Satuan Pendidikan Ramah Anak pada Tingkat Madrasah - Bakhtiar, Nurhasanah; Afrida, Afrida; Mukhtar, Nurkamelia; Putri, Al Miftah Diana (MENARA RIAU, 2024)
The purpose of this service is to help madrasahs meet the stages and indicators of child-friendly schools, so that madrasahs become a safe and comfortable place for children who are ultimately able to improve the quality and quality of madrasahs. This method of service uses the ABCD (Asset Based Community Development) approach. Through the ABCD approach, madrasah assets are empowered in the form of human resources and existing facilities to realize child-friendly schools. The target of this service is 22 madrasahs in the city of Pekanbaru starting from level 8 Raudhatul Athfal, 6 Madrasah Ibtidaiyah, 4 Madrasah Tsanawiyyah and 4 Madrasah Aliyah. Program evaluation is carried out through direct observation and filling out an online questionnaire (G-Form). The result of this service is to provide assistance to 22 madrasahs starting from stage 1) Pre-Mentoring; coordination with related parties 2) Implementation of Assistance; with several activities, namely: (a) carrying out joint declarations, (b) training on madrasah policy formulation towards CFS, (c) direct assistance to RAs and Madrasahs, (d) giving rewards to 6 madrasahs that have commitment and MAU towards Child Friendly Education units. This mentoring evaluation shows the achievement of the target of declaring 22 madrasahs towards child-friendly schools, school principals can understand the formulation of madrasah policies towards CFS, and increase the motivation of madrasahs to go to CFS with rewards.